2007
DOI: 10.1016/j.ydbio.2007.04.002
|View full text |Cite
|
Sign up to set email alerts
|

SCL-GFP transgenic zebrafish: In vivo imaging of blood and endothelial development and identification of the initial site of definitive hematopoiesis

Abstract: The bHLH transcription factor SCL plays a central role in the generation of hematopoietic cells in vertebrates. We modified a PAC containing the whole zebrafish scl locus, inserting GFP into the first coding exon of scl. In germline-transgenic zebrafish generated using this construct, GFP expression completely recapitulates the endogenous expression of scl in blood, endothelium and CNS. We performed in vivo timelapse imaging of blood and endothelial precursor migration at the single-cell level and show that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
60
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(64 citation statements)
references
References 79 publications
3
60
1
Order By: Relevance
“…5G). Thus, clearly the PLM contains precursors of both blood and endothelium at early somitogenesis stages (as already shown by Vogeli et al, 2006;Zhang and Rodaway, 2007). However, the existence of 'hemangioblasts' in the PLM awaits the labeling of single cells within this population.…”
Section: The Hemangioblastmentioning
confidence: 65%
“…5G). Thus, clearly the PLM contains precursors of both blood and endothelium at early somitogenesis stages (as already shown by Vogeli et al, 2006;Zhang and Rodaway, 2007). However, the existence of 'hemangioblasts' in the PLM awaits the labeling of single cells within this population.…”
Section: The Hemangioblastmentioning
confidence: 65%
“…Approximately 8 kb of the 5¢ upstream sequence of tal1 [24,25] was polymerase chain reaction (PCR)-amplified from zebrafish genomic DNA. The amplified tal1 promoter, EGFP, and SV40 poly(A) were placed in the pT2KXIGDin vector that has Tol2 transposable elements [26].…”
Section: Generation Of Tg(tal1:egfp) Fishmentioning
confidence: 99%
“…The CHT is similar to mouse placenta or fetal liver, and developing lymphoid and myeloid cells in this region can be identified by markers such as c-myb, scl, runx1, and ikaros (Murayama et al 2006;Zhang and Rodaway 2007). Thymic immigrants differentiate into rag1 + lymphoid cells (Murayama et al 2006;Jin et al 2007;Kissa et al 2008).…”
Section: Embryonic Hematopoiesis: Primitive and Definitive Wavesmentioning
confidence: 99%
“…Live imaging of cells labeled with green fluorescent protein (GFP) driven by HSC-specific promoters, such as CD41 and c-myb, and caged fluorescein-dextran cell-tracing experiments have shown that HSCs from the AGM region migrate to colonize the CHT, thymus, and pronephros (Murayama et al 2006;Jin et al 2007;Zhang and Rodaway 2007;Bertrand et al 2008;Kissa et al 2008). CD41 marks HSCs in the mouse (Mitjavila-Garcia et al 2002;Ferkowicz et al 2003;Mikkola et al 2003).…”
Section: Migratory Routes Of Hscs To Secondary Hematopoietic Sitesmentioning
confidence: 99%